Legal Implications of Making a Certificate of Inheritance That Does Not Match the Heirs' Statement - Yantin, Tri (Jurnal Konstatering, 2024)
This study aims to analyze: 1) The legal implications of making a certificate of inheritance that does not match the information of the heirs can be considered invalid or does not have sufficient legal force to determine a person's inheritance rights. However, the Certificate of Inheritance is still valid as long as it is not stated that the deed is invalid by the Court Judge. Making a certificate of inheritance that does not match the information of the heirs will have legal implications. However, it does not have any legal consequences for the Notary, because the Notary is only a public official who is authorized to make a deed according to the information or wishes or legal acts given by the parties. 2) The notary's responsibility for making a certificate of inheritance that does not match the information of the heirs will not have legal consequences for the notary himself and the notary cannot be held accountable for anything, the party in the deed is responsible if the deed contains incorrect information, because the contents of the deed are the will of the parties, not the Notary. Except if the Notary participates in making incorrect information in order to gain profit, then it can result in the Notary also being prosecuted. Notary YP in this case does not need to be held criminally or civilly responsible for the legal acts he has committed, because in court it was proven that he did not violate any criminal or unlawful acts, so Notary YP does not need to be held legally responsible. The principle of responsibility held by a Notary, adheres to the principle of responsibility based on fault of liability, the Notary cannot be held accountable. Because, the Notary only records what has been conveyed by the parties and then the Notary pours what has been conveyed into the deed.